Effectiveness of Emotion Regulation Training on Reduction of Anxiety, Stress and Depression Symptoms among University Students - Naser Sobhi-Gharamaleki; Parviz Porzoor; Seifollah Aghajani; Mohammad Narimani (Iranian Association of Health Education and Health Promotion, 2015)
Background and objective: Stress, anxiety and depression, as mental health factors, creates several problems for students - the country's future generation. The purpose of this study was to determine the effectiveness of emotion regulation training on the reduction of Anxiety, Stress and Depression symptoms among university students. Methods: In this semi-experimental research a pre-post test and a control group was used. For this purpose, 186 male students using multistage cluster were selected and stress, anxiety and depression questionnaire were performed on all of them. After filling out the questionnaire, from students with a score of 28 or more, 40 ones were randomly selected and were divided into two groups- under training and control. The experimental group received emotion regulation training and the control group did not receive the training. Training was performed in the experimental group for eight sessions (two sessions a week and each half an hour) on all subjects. Before the training and after that, the Depression, Anxiety and Stress Scale was completed. The descriptive statistics and MANCOVA were used to analyze the data. Results: Analysis of covariance showed that the anxiety, stress and depression scores of student in the emotion regulation training group compared to the control group at posttest hadreduced (P<0.001). Conclusion: Therefore emotion regulation training significantly reduces the symptoms of anxiety, stress and depression. These results have important implications in the field of mental health of students. Paper Type: Research Aricle.